An effective continuous-time formulation for scheduling optimization in a shipbuilding assembly process - Basán, Natalia Paola (2018)
This work aims at finding an optimal solution of assembly operations in a system of multi-stage production in a shipyard. Shipbuilding of large-size ships is a complex manufacturing process involving the production and assembly of a big quantity of blocks. These blocks are then assembled on the block erection final process, with a predefined order. To achieve competitiveness in this market, the development of efficient operation strategies is a potential alternative. To reach this objective, a mixed-integer linear mathematical model (MILP) is proposed. The model is based on the continuous time-slot time batches concept. This mathematical formulation allows obtaining efficient solutions to academic problems with reasonable computational effort. The MILP problem was tested and computational experiences were reported for industrial problems.